The Noise of Walking - Salm, Twyla; Brogden, Lace Marie (Journal of the Canadian Association for Curriculum Studies, 2021)
Walking pedagogies provide opportunities for embracing diversity, at the same time that they honour a relationship with the Earth. As such, they can be used to encourage learners and curriculum makers to attune to their surroundings. Walking and writing together, though from disparate geographical locations, we provoke critical reflections on ableism through walking pedagogies. Inspired by our surroundings, we explicate and query curriculum experiences and the pedagogical reflections that accompany them/us, holding space for (dis)abilities. Co-constructed poetries frame our autoethnographic engagements with theory and practice. We offer two ways walking pedagogies may be engaged to disrupt ableism: walking to “disorient the norm” (Parrey, 2020) in the first instance, and moving as listening in the second. Through these disruptions to ableist discourses, we attend to ongoing circumstances of curriculum-making, attuning to the noise of walking in nature, where some have unrestricted access, some have partial access and some have no access at all.